Effect of Post-harvest Application of Salicylic Acid on the Storage Stability of Peach Fruit: Application of Salicylic Acid on Peach Fruit (Biological Sciences - PJSIR, 2022)
Post-harvest storage stability of peach fruit was studied at 4 ± 1 °C for five weeks with different concentration of salicylic acid (1.5 mM, 2.0 mM, 2.5 mM, 3.0 mM). Peach fruit dipped in distilled water are considered as control. The fruits were packed in Styrofoam boxes and stored for five weeks. All the treatments were analyzed physio-chemically i.e. weight loss, firmness, TSS, pH, titratable acidity, sugar acid ratio, ascorbic acid and chilling injury and organoleptically i.e. flavour, colour, texture and overall acceptability at every 7 days interval during 5 weeks of storage. Overall results showed a continuous decrease in fruit firmness (from 74.61-35.37 N), titratable acidity (from 0.82-0.52%), ascorbic acid (from 7.34-4.85 mg/100 g), colour (from 8.8-3.7), flavour (from 8.5-5.2), texture (from 8.2-4.6) and overall acceptability (from 8.5-4.5), while an increase in weight loss (from 0-16.92%), TSS (from 7.84-10.18°Brix), pH (from 3.84-4.29), sugar acid ratio (from 9.58-19.72) and chilling injury index (from 0-2.30) noted throughout storage period. The maximum mean value for fruit firmness was recorded in 2.5 mM dipped treatment was (64.63 N), weight loss in 0 mM dipped treatment was (9.81), TSS in 2.5 mM dipped treatment was (9.24), pH in 0 mM dipped treatment was (13.95), acidity in 2.5 mM dipped treatment was (0.69), sugar acid ratio in 0 mM dipped treatment was (13.95), ascorbic acid in 2.5 mM dipped treatment was (6.69), chilling injury in 0 mM dipped treatment was (1.17), colour in 2.5 mM dipped treatment (7.7), flavour in 2.5 mM dipped treatment (7.7), texture in 2.5 mM dipped treatment (7.7) and overall acceptability in 2.5 mM dipped treatment (7.7). It was evident from statistical analysis that storage and treatments had a significant effect on the storage stability of peach fruits. On the basis of overall physio-chemical and sensory analysis, it was concluded that 2.5 mM dipped treatment showed the best results followed by 3.5 mM dipped treatment.